Endothelial-Leukocyte Interaction in Severe Malaria: Beyond the Brain - Mariana C. Souza; Tatiana A. Padua; Maria G. Henriques (Mediators of Inflammation)
Malaria is the most important parasitic disease worldwide, accounting for 1 million deaths each year. Severe malaria is a systemic illness characterized by dysfunction of brain tissue and of one or more peripheral organs as lungs and kidney. The most severe and most studied form of malaria is associated with cerebral complications due to capillary congestion and the adhesion of infected erythrocytes, platelets, and leukocytes to brain vasculature. Thus, leukocyte rolling and adhesion in the brain vascular bed during severe malaria is singular and distinct from other models of inflammation. The leukocyte/endothelium interaction and neutrophil accumulation are also observed in the lungs. However, lung interactions differ from brain interactions, likely due to differences in the blood-brain barrier and blood-air barrier tight junction composition of the brain and lung endothelium. Here, we review the importance of endothelial dysfunction and the mechanism of leukocyte/endothelium interaction during severe malaria. Furthermore, we hypothesize a possible use of adjunctive therapies to antimalarial drugs that target the interaction between the leukocytes and the endothelium.